Simulation of dimethyl ether production as LPG substitute using LNG from Arun terminal with tri-reforming and direct synthesis method - Rahmatullah, Faiprianda Assyari; Pamungkas, Tegar; Mutia, Sarah; Zulfansyah, Zulfansyah; Rionaldo, Hari (Universitas Lambung Mangkurat, 2024)
Increased demand for LNG compels Indonesia to import to meet these needs. Substituting LNG with alternative fuel emerges as a strategy to reduce LPG imports. One such alternative can be used for LPG substitution is Dimethyl Ether. Dimethyl ether is a colorless compound possesses a heating value of 30,5 MJ/kg and an energy equivalency with LPG ranging between 1,56 – 1,76. Dimethyl ether can be directly synthesized from synthetic gas produced through natural gas reforming. Production of synthetic gas from natural gas employs the tri-reforming method which integrating steam reforming, dry reforming, and partial oxidation methods in a single reactor offering optimal energy utilization advantages and minimal environmental impact. Dimethyl ether production from synthetic gas is using direct synthesis method, combining methanol synthesis and dehydration in a single reactor providing high conversion advantages compared to indirect synthesis method. Simulation was carried out using process simulator program ASPEN Plus V11. Based on the simulation results, dimethyl ether yield and selectivity is 99.62%.